2014
DOI: 10.1002/lt.23940
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-assisted hepatectomy versus conventional (open) hepatectomy for living donors: When you know better, you do better

Abstract: The conventional incision for donor hepatectomy is a right subcostal incision with a midline extension. With increased experience in both donor hepatectomy and laparoscopy, the conventional incision can be shortened to a significant extent. Laparoscopic mobilization of the liver coupled with a hand port allows the insertion of one hand inside the abdomen for control; this makes small-incision donor hepatectomy a technically feasible alternative. We compared 26 right lobe donor hepatectomies performed with a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 16 publications
1
56
0
Order By: Relevance
“…The level of evidence of these articles was estimated using the United Kingdom Cochrane Centre of Evidence (2001)[28]. Six articles described cohort studies comparing contemporary series of patients (level of evidence: 2b)[12,16,19-22]; five articles were retrospective case-control studies (level of evidence: 3b)[13-15,18,24], and two articles were retrospective studies using historical series as controls (level of evidence: 4)[17,23]. …”
Section: Methodsmentioning
confidence: 99%
“…The level of evidence of these articles was estimated using the United Kingdom Cochrane Centre of Evidence (2001)[28]. Six articles described cohort studies comparing contemporary series of patients (level of evidence: 2b)[12,16,19-22]; five articles were retrospective case-control studies (level of evidence: 3b)[13-15,18,24], and two articles were retrospective studies using historical series as controls (level of evidence: 4)[17,23]. …”
Section: Methodsmentioning
confidence: 99%
“…Our results demonstrated that LLDH was associated with significantly longer operative time, which could be explained by the frequent installation and removal of laparoscopic devices, mobilization and dissection the lobe of the liver under laparoscopy as well as surgeons’ experience and initial learning curve[26, 27]. Meanwhile, the operative time difference between LLDH and OLDH might correlate with the type of hepatectomy.…”
Section: Discussionmentioning
confidence: 92%
“…Four studies were conducted in Korea[22, 23, 25, 27], one in the United States[21], one in France[12], one in China[24]. , one in Japan[13], and one in India[26]. The sample size of the included studies ranged from 22 to 493 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations